1999
DOI: 10.1093/humrep/14.1.190
|View full text |Cite
|
Sign up to set email alerts
|

The cyclic pattern of the immunocytochemical expression of oestrogen and progesterone receptors in human myometrial and endometrial layers: characterization of the endometrialsubendometrial unit

Abstract: Immunocytochemistry of oestrogen receptor (ER) and progesterone receptor (PR) expression of the whole uterine muscular wall and the endometrium was performed in order to obtain morphological and functional insights into the regulation of cyclic uterine peristalsis, which is confined to the endometrium and the subendometrial myometrium and serves functions such as rapid and sustained sperm transport. The study revealed that the subendometrial myometrium or stratum subvasculare with a predominantly circular arra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
115
0
30

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(153 citation statements)
references
References 37 publications
8
115
0
30
Order By: Relevance
“…Other studies suggest that smooth muscle proliferation and hyperplasia in the JZ may precede the outgrowth of endometrial cells and adenomyosis. 1,[33][34][35] The term JZ hyperplasia was coined to define partial or diffuse thickening of the JZ; it does not necessarily indicate the presence of adenomyosis but that disruption of JZ architecture may constitute the primary event in the development of adenomyosis and infertility by altering uterus peristalsis. 6,[35][36][37] It seems that endometriosis, JZ abnormalities, and adenomyosis could represent phenotypes of a similar endomyometrial dysfunction syndrome rather than different diseases.…”
Section: Commentmentioning
confidence: 99%
“…Other studies suggest that smooth muscle proliferation and hyperplasia in the JZ may precede the outgrowth of endometrial cells and adenomyosis. 1,[33][34][35] The term JZ hyperplasia was coined to define partial or diffuse thickening of the JZ; it does not necessarily indicate the presence of adenomyosis but that disruption of JZ architecture may constitute the primary event in the development of adenomyosis and infertility by altering uterus peristalsis. 6,[35][36][37] It seems that endometriosis, JZ abnormalities, and adenomyosis could represent phenotypes of a similar endomyometrial dysfunction syndrome rather than different diseases.…”
Section: Commentmentioning
confidence: 99%
“…It is estimated that <50% of uterine myomas produce symptoms, and they are usually discovered by clinical examination. Although the etiology of uterine fibroids is unknown, their development is considered to be estrogen dependent, because they have the ability to enlarge during pregnancy and to shrink during menopause, ovariectomy, and other hypoestrogenic conditions (2)(3)(4). Aromatase P450 is often overexpressed in myomas, causing in situ synthesis of estrogen to increase, and this is believed to contribute to the growth of leiomyomas (5).…”
mentioning
confidence: 99%
“…There is also conflicting evidence as regards the relative abundance of the two forms of ER in the fibroids and how this could impact fibroid response to hormonal therapy, because some studies report that the ERa-to-ERb ratio is higher in the diseased tissue compared with normal (22), whereas others report an increase in the ERa-to-ERb ratio after treatment with a GnRH analogue (21). In addition, it has been reported that the levels of ERa and ERb in myometrial cells change during the menstrual cycle and that the patterns of changes are similar (4). The present study aims at estimating mRNA and protein levels as compared with the DNA-binding activities of two ER subtypes in leiomyomas and normal myometrium during the follicular phase of the menstrual cycle.…”
mentioning
confidence: 99%
“…However, during pregnancy they increase greatly in size and may attain a length of approximately 600µm. The muscle fibres are arranged into two layers; the stratum subvasculare, which lies below the endometrium and stratum supravasculare (Leeson et al, 1988;Noe et al, 1999). It is generally known that thinning of the myometrium occurs after menopause.…”
Section: Ovaries and The Biology Of Menopause: The Role For Inhibin Imentioning
confidence: 99%
“…Both the strata vasculare and supravasculare have oestrogen and progesterone receptors. Nonetheless, during reproductive life the stratum vasculare is much more dynamic than stratum supravasculare (Noe et al, 1999). The smooth muscle cell exhibits a cyclic pattern of sex hormones receptor expression that is comparable to those in the endometrium (Koshiyama et al, 1996;Noe et al, 1999).…”
Section: Ovaries and The Biology Of Menopause: The Role For Inhibin Imentioning
confidence: 99%